The optimization of transport flows crossing Lithuanian custom-houses - Jarašūnienė, Aldona (Transport, 2002)
The importance of the experience of foreign countries, the improvement of the nonnative and law basis according to improvement standards, the employment of means of information are emphasized in the article. The investigation of road transport distribution on lines showed that the distribution depends on the flow law of arriving vehicles. It was proved that the distribution of vehicles according to time and the distribution of vehicles on different lines can be defined by the Erlang law of distribution of the 2nd sequence. First Published Online: 19 Oct 2011